Galea and periosteum flap filled with bone fragments in rabbits - Brock, Ryane Schmidt; Viterbo, Fausto [UNESP]; Capel, Guilherme; Domingues, Maria Aparecida Custódio [UNESP]; Paschoalinotte, Eloísa Elena; Labbé, Daniel [UNESP] (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2013)
PURPOSE: To study the bone viability of a vascularized galea and periosteum flap filled with bone fragments, as a substitute of the bone graft in facial reconstructive surgery. METHODS: Forty rabbits were studied, and divided in two groups. One had a simple galea and periosteum flap done and the other had the same flap done and filled with bone fragments of the calvaria. The bone formation was evaluated by radiographies, macroscopic and microscopic analysis. RESULTS: The bone neoformation in both groups with differences in bone morphology and structure especially at histological analysis. CONCLUSION: This study demonstrated osseous formation in both groups of galea and periosteum flaps, with and without bone fragments.
Keywords: Bone; Skull; Surgical Flaps; Reconstruction; Grafts; Rabitts